Computational Study of Inverted All-Inorganic Perovskite Solar Cells Based on CsPbIxBr3-X Absorber Layer with Band Gap of 1.78 eV - Martinez, Nahuel (2020)
All-inorganic perovskite solar cells (PSCs) with inverted p-i-n configuration have not yet reached the high efficiency achieved in the normal n-i-p architecture. However, the inverted all-inorganic PSC are more compatible with the fabrication of tandem solar cells. In this work, a theoretical study of all-inorganic PSCs with inverted structure ITO/HTL/CsPbIxBr3−x/ETL/Ag, has been performed by means of computer simulation. Four p‐type inorganic materials (NiO, Cu2O, CuSCN and CuI) and three n-type inorganic materials (ZnO, TiO2 and SnO2) were used as hole and electron transport layers (HTL and ETL), respectively. A band gap of 1.78 eV was used for the CsPbI x Br3−x perovskite layer. The simulation results allow identifying that CuI and ZnO are the most appropriate materials as HTL and ETL, respectively. Additionally, optimized values of thickness, acceptor density and defect density in the absorber layer have been obtained for the ITO/CuI/CsPbI x Br3−x /ZnO/Ag, from which, an optimum efficiency of 21.82% was achieved. These promising theoretical results aim to improve the manufacturing process of inverted all-inorganic PSCs and to enhance the performance of perovskite–perovskite tandem solar cells.